Analisis Mediasi Brand Awareness dan Brand Trust dalam Hubungan Emotional Marketing dengan Purchase Intention - Achmad Yanu Alif Fianto; Helmy Widyantara; Dominggo Bayu Baskara (JMK (Jurnal Manajemen dan Kewirausahaan), 2022)
This study and analysis was carried out to examine the effect of emotional marketing on purchase intention. This study also analyzes the mediating role of brand awareness and brand trust in the relationship between emotional marketing and purchase intention. This study uses a questionnaire as an instrument of study and has collected valid and reliable data from 130 respondents who are users of MSME products who are actively promoting on Instagram social media. This study adopted the Structural Equation Model (SEM) with the Partial Least Square (PLS) technique to test the hypothesis in this study. This study proves that brand awareness and brand trust have a mediating role in the relationship between emotional marketing and purchase intention. This means that emotional marketing has an indirect effect on purchase intention through brand trust and brand awareness. This study also proves that emotional marketing does not have a significant impact on purchase intention.